Social representations on Democracy in Latin American university students - Ruiz-Pérez, José Ignacio (2021)
The aim was to know the structure, basic cognitive schemes (BCS) and dimenssions on social representations of Democracy, in several Iberoamerican contexts. Non-randomized samples of university students from 5 countries: Colombia, El Salvador, Argentina, Perú and Spain, answered a task on word association about Democracy and BCS identification. In therms of results, “Liberty”, “Justice”, “Equality” and “Law” were the words concerning the central nucleus of “Democracy”. According BCS scores, democracy was a more central theme for Salvatorian students, and less central for Peruvians.